Achieving Successful VLC Signal Reception Using A Rolling Shutter Image Sensor While Driving at 40 km/h - Shunki Kamiya; Zhengqiang Tang; Takaya Yamazato; Masayuki Kinoshita; Koji Kamakura; Shintaro Arai; Tomohiro Yendo; Toshiaki Fujii (IEEE Photonics Journal, 2023)
This paper presents the successful reception of visible light communication (VLC) signals, transmitted from an LED array, by an image sensor that utilizes a rolling shutter while driving at 40 km/h. The rolling shutter image sensors used in commercial cameras, such as those found in smartphones and dashcams, capture images line by line at a fast rate, allowing for VLC signal reception in vehicular environments. By analyzing the relationship between the signal reception rate for each line and the frame rate, we demonstrate that parallel VLC signals transmitted from the LED array can be received even while in motion. Notably, to our knowledge, this is the first time that an automobile moving at 40 km/h has successfully received a VLC signal.